Faktor yang Mempengaruhi Opini Going Concern Dimoderasi Koneksi Politik - Tarigan, Kaninta Agnes Melati; Wijayanti, Anita (Jurnal Ilmiah Wahana Akuntansi, 2024)
This research aims to analyze how financial conditions, managerial ownership and foreign ownership affect going concern audit opinions with political connection as a moderating variable. The population includes real estate companies listed on the Indonesia Stock Exchange (BEI) in 2018-2021, from which the samples of 29 companies with 116 units of analysis are selected through purposive sampling. Hypotheses are tested by logistic regression analysis processed by IBM SPSS 26; and the results indicate that financial condition and foreign ownership have a negative effect on going-concern audit opinion while managerial ownership has no effect on going-concern audit opinion. Political connection moderates the effect of foreign ownership on going-concern audit opinion but does not moderate financial condition and managerial ownership. The novelty of this research exhibits the use of political connection as one of the factors that makes companies obtain going-concern audit opinions, and this research is expected to contribute to company development.